Analisis Portofolio Optimal Saham Indeks Lq-45 Dengan Model Indeks Tunggal Di Bursa Efek Indonesia - ALMUNFARIJAH ALMUNFARIJAH (Universitas Mercu Buana Yogyakarta, 2017)
Rational investors invest in efficient stocks, the stocks that have high return with minimum risk. The sample in this study using the stocks in the group LQ-45 index during the period February 2013-July 2013. The purpose of the study was to establish the optimal portfolio and to know the difference between stock returns and the risk of candidate and non-candidate portfolirn On Equity (ROE).The results showed there were 15 stocks that become candidate in a portfolio out of 45 stocks studied with the cut of point value -2.7-7. Optimal portfolio is formed by 15 stocks that have excess returns to beta (ERB) which is greater than the risk-free return (Rf).The largest proportion of funds owned by PT Kalbe FarmaTbk i.e 16,2 %, and the smallest proportion of the funds owned by PT Bank Central Asia Tbk i.e 0,1101288%. Rational investor would prioritize to invest in securities that have a the largest proportion of the funds, because of that large proportion of funds so we will be getting higher profit with the certain risks as well.Investors that will invest theirs funds into these 15 companies that have formes this optimal portfolio would get portfolio profit 2,1-7 and portfolio risk -2.7-7. That portfolio profit is not far different with the expected return of each individual stock. So despite using LQ-45 stocks that have the biggest marketing capitalization and the most liquid infact it has not guarante that investors would gain their expectation of getting portfolio return as what they expected.Risk portfolio of 2,1-7 is smaller than the risk level of each individual stock . Although the establishment of the optimal portfolio yield expected return of portfolio which is not much different with thereturn of individual stock,but still provide the benefit of diversification that is beneficial for reducing the risk of each individual stock